2015
DOI: 10.3168/jds.2014-8905
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Holstein-Friesian and Norwegian Red dairy cattle for estrus length and estrous signs

Abstract: This study addressed the effect of breed on estrus length and estrous behavior by observing 20 Holstein-Friesian (HF) and 20 Norwegian Red (NRF) cows on an outdoor wood-chip pad through 1 estrous cycle (22d). Detailed behavioral data were collected by continuous (24 h) video monitoring of all cows. Accurate estimation of duration of estrous periods, behavioral signs (sum per period and counts per hour), and duration and number of sexually active groups were reported through all stages of mount estrus (prestand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 35 publications
5
13
0
Order By: Relevance
“…Swedish Holstein cows tend to prioritize milk yield and go into a faster and deeper NEB than SR cows (Berglund & Danell, 1987;Hjertén, 2006). The breed difference is in agreement with Sveberg et al (2015), who found that the Norwegian Red cows expressed more STBM and mounting activity, whereas HF cows expressed more secondary symptoms, which indicates a higher overall OI in the Norwegian Red cow.…”
Section: Discussionsupporting
confidence: 79%
“…Swedish Holstein cows tend to prioritize milk yield and go into a faster and deeper NEB than SR cows (Berglund & Danell, 1987;Hjertén, 2006). The breed difference is in agreement with Sveberg et al (2015), who found that the Norwegian Red cows expressed more STBM and mounting activity, whereas HF cows expressed more secondary symptoms, which indicates a higher overall OI in the Norwegian Red cow.…”
Section: Discussionsupporting
confidence: 79%
“…The results of our study seem to indicate that differences in the reproductive parameters between breeds within the same organic farm may be related to differences in expression of oestrus, which farmers must be able to identify before the cows are inseminated. Oestrous duration is much shorter in Holstein‐Friesian than in Norwegian Red cows, which also participate in greater number of sexually active groups for longer and display different (more frequent) mounting activity (Sveberg et al, ). Similar results were obtained in a study comparing Holstein‐Friesian with Normande cows, with the former showing less obvious signs of oestrus (Cutullic, Delaby, Causer, Michel, & Disenhaus, ).…”
Section: Discussionmentioning
confidence: 99%
“…Oestrous duration is much shorter in Holstein-Friesian than in Norwegian Red cows, which also participate in greater number of sexually active groups for longer and display different (more frequent) mounting activity (Sveberg et al, 2015). Similar results were obtained in a study comparing Holstein-Friesian with Normande cows, with the former showing less obvious signs of oestrus (Cutullic, Delaby, Causer, Michel, & Disenhaus, 2009 The Holsteinisation phenomenon affects female fertility (Buaban et al, 2015;Lindhé & Philipsson, 1998;Royal et al, 2000), which can be explained by the more intense selection for milk production in the Holstein-Friesian breed (Dillon, Berry, Evans, Buckley, & Horan, 2006;Pryce, Royal, Garnsworthy, & Mao, 2004 (Walsh et al, 2007(Walsh et al, , 2008.…”
Section: Comparison Of Reproductive Parameters Of Holstein-friesianmentioning
confidence: 99%
“…The modern dairy cow is only in estrus for an average of 6-8 hours (Sveberg et al, 2015) and stands to be mounted an average of 4 times (Palmer, Olmos, Boyle, & Mee, 2010). All of these factors have led to the popularity of synchronization technology.…”
Section: Reproductive Technologymentioning
confidence: 99%